[Laiškas] / Meištovičius (Meysztowicz) Adomas - Mykolui Zaleskiui. - (:unkn) unknown (My University, 1800)
1 laiškas apie atvykimą į Šeibakpolį dėl dvaro padalijimo.
Keywords: Rankraščiai; Laiškai; Autografų kolekcija; Meištovičius (Meysztowicz), Adomas; Zaleskis, Mykolas